How Socioeconomic Status Affects Patient Perceptions of Health Care: A Qualitative Study - Nicholas C. Arpey; Anne H. Gaglioti; Marcy E. Rosenbaum (SAGE Publishing, 2017)
Introduction: Clinician perceptions of patients with low socioeconomic status (SES) have been shown to affect clinical decision making and health care delivery in this group. However, it is unknown how and if low SES patients perceive clinician bias might affect their health care. Methods: In-depth interviews with 80 enrollees in a state Medicaid program were analyzed to identify recurrent themes in their perceptions of care. Results: Most subjects perceived that their SES affected their health care. Common themes included treatment provided, access to care, and patient-provider interaction. Discussion: This study highlights complex perceptions patients have around how SES affects their health care. These results offer opportunities to reduce health care disparities through better understanding of their impact on the individual patient-provider relationship. This work may inform interventions that promote health equity via a multifaceted approach, which targets both providers and the health care system as a whole.